Effect of litter size on prepartum metabolic and amino acidic profile in rabbit does. (11th October 2020) - Minuti, A.; Gallo, A.; Lopreiato, V.; Bruschi, S.; Piccioli-Cappelli, F.; Uboldi, O.; Trevisi, E.
Abstract : The use of modern prolific lines of rabbit does in intensive production systems leads to an increase in productivity but also causes a rise in several problems related to the does' health status. Hence, the aim of this study was to investigate the effect of the litter size on the metabolic, inflammatory and plasma amino acid profile in rabbit does. The blood of 30 pregnant does was sampled on the 27th day of pregnancy. The does were retrospectively grouped according to the number of offspring into a high litter size group (HI, does with ≥ 12 kits; n = 16) and a low litter size group (LO, does with ≤ 11 kits; n = 14). Data were subjected to Pearson's correlation analysis. Further, data were analysed in agreement to a completely randomized design in which the main tested effect was litter size. The linear or quadratic trends of litter size on parameters of interests were post hoc compared by using orthogonal contrasts. In addition, compared with the LO group, the HI group had lower levels of glucose (−5%; P < 0.01), zinc (−19%; P < 0.05), albumin (−6%; P < 0.05) and total cholesterol (−13%; P < 0.07), but the total bilirubin level was higher in the HI group (+14%; P < 0.05). Regarding the plasma amino acids, the HI group had lower concentrations of threonine (−15%), glycine (−16%), lysine (−16%) and tryptophan (−26%) and a higher level of glutamic acid (+43%; P < 0.05) compared with the LO group. The exclusively ketogenic amount of amino acids was lower ( P < 0.06) in the HI (55.8 mg/100 ml) does compared with the LO does (56.8 mg/100 ml). These results show that a few days before delivery, rabbit does that gave birth to a higher number of offspring had a metabolic profile and an inflammatory status that was less favourable with respect to does who gave birth to a lower number of offspring. Moreover, the plasma amino acid profile points out that there was an enhanced catabolic condition in the rabbit does with a high number of gestated foetuses; it was likely related to the greater energy demand needed to support the pregnancy and an early inflammatory response.